2018
DOI: 10.2196/jmir.9523
|View full text |Cite
|
Sign up to set email alerts
|

Public Awareness, Usage, and Predictors for the Use of Doctor Rating Websites: Cross-Sectional Study in England

Abstract: BackgroundWith the advent and popularity of social media and consumer rating websites, as well as the emergence of the digitally engaged patient, there has been an increased interest in doctor rating websites or online patient feedback websites, both inside and outside academia. However, there is very little known about how the public across England views such rating websites as a mode to give patient experience feedback.ObjectiveThe aim of the overall study was to measure and understand public awareness, usag… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 40 publications
0
17
1
1
Order By: Relevance
“…36 Although there are some caveats in the non-comparability of studies that have been conducted in different settings, using different questionnaires, it seems that the number of people using online feedback is rising rapidly from a very low baseline over time. Subsequent to undertaking this project, a separate study 108 conducted in 2016 has been published examining the prevalence of knowledge and use of online feedback specifically in relation to UK general practice, showing a very low prevalence of usage in relation to feedback specifically about GPs (0.4% prevalence), in combination with a low awareness among the public of GP rating sites (15% awareness).…”
Section: Introductionmentioning
confidence: 99%
“…36 Although there are some caveats in the non-comparability of studies that have been conducted in different settings, using different questionnaires, it seems that the number of people using online feedback is rising rapidly from a very low baseline over time. Subsequent to undertaking this project, a separate study 108 conducted in 2016 has been published examining the prevalence of knowledge and use of online feedback specifically in relation to UK general practice, showing a very low prevalence of usage in relation to feedback specifically about GPs (0.4% prevalence), in combination with a low awareness among the public of GP rating sites (15% awareness).…”
Section: Introductionmentioning
confidence: 99%
“…The use of PRWs first requires the public to be aware of them [38]. Recent studies in the United States and Germany suggest that a lack of awareness is no longer a key barrier to PRW usage in these countries [38-41], although a recent study in the England found public awareness of PRWs to still be very low [42]. However, despite the fact that awareness of PRWs is an important factor, it should be noted that although the studies conducted in the United States and Germany found high awareness of the PRWs, the level of PRW usage was still found to be comparable with previous studies [3,43], suggesting that even if awareness of PRWs increases, there are other factors behind the low level of physician ratings.…”
Section: Discussionmentioning
confidence: 99%
“…8). Recent studies show that the online reviews of an HCP directly affect the number of patient visits and question their skills on particular specialties [15]- [17]. From the table-III, we get to know that about 66.9% of the HCPs do not have any professional online presence.…”
Section: Fig 8: Online Presence On Patient Review Websitesmentioning
confidence: 99%